2008
DOI: 10.1089/tea.2007.0200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Corneal Stromal Layer with Dermal Fibroblasts: Phenotypic and Functional Switch of Differentiated Cells in Cornea

Abstract: Previously, we successfully engineered a corneal stromal layer using corneal stromal cells. However, the limited source and proliferation potential of corneal stromal cells has driven us to search for alternative cell sources for corneal stroma engineering. Based on the idea that the tissue-specific environment may alter cell fate, we proposed that dermal fibroblasts could switch their phenotype to that of corneal stromal cells in the corneal environment. Thus, dermal fibroblasts were harvested from newborn ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, alternative cell sources should be tested. In our previous study, we reported that dermal fibroblasts could switch their phenotype to keratocytes in the cornea stromal environment [ 34 ]. Using such cells should therefore be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alternative cell sources should be tested. In our previous study, we reported that dermal fibroblasts could switch their phenotype to keratocytes in the cornea stromal environment [ 34 ]. Using such cells should therefore be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In our previous study, DFs were observed to undergo a phenotypic and functional switch to cornea stromal-like cells when implanted in a corneal stromal layer without induction. 9 These findings suggest that DFs may possess the capability of transdifferentiating into other cell types when offered with a suitable inducing agent or microenvironment.…”
Section: Introductionmentioning
confidence: 92%
“…23 For example, DFs were successfully used as seed cells to regenerate corneal stromal layer and tendon via tissue engineering technique. [24][25][26] In this study, DFs were used as seed cells to regenerate spinal dura tissue, which was inspired by the fact that spinal dura was composed of highly oriented collagen fibers as matrix lined with small amount of fibroblasts. It was then shown that histological structure of the reconstructed tissue of the experimental group bore great similarity to that of normal one.…”
Section: Discussionmentioning
confidence: 99%